2017
DOI: 10.1177/1535370217728460
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31 inhibits RhoA-mediated tumor invasion and chemotherapy resistance in MKN-45 gastric adenocarcinoma cells

Abstract: microRNAs are small single-stranded non-coding RNA molecules which modify gene expression by silencing potential target genes. The aberrant expression of RhoA, a small GTPase protein of Rho family, is involved in gastric cancer tumorigenesis. Since miR-31 is a pleomorphic molecule, we evaluated the miR-31/RhoA axis in inducing the malignant phenotype of gastric cancer cells MKN-45. Also, the clinicopathological significance of RhoA was investigated in a well-defined collection of gastric carcinomas which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 31 publications
(46 reference statements)
2
41
2
Order By: Relevance
“…In addition, miR‐146a suppresses RhoA expression in MDA‐MB231 cells (Liu et al, ). Another microRNA, miR‐31, also reduced RhoA expression in gastric cancer cells MKN‐45 (Korourian, Roudi, Shariftabrizi, & Madjd, ). Loss of miR‐122 was also shown to be associated with poor prognosis in hepatocellular carcinoma progression along with cell migration and invasion and interestingly, RhoA 3′ UTR may be a binding site for miR‐122 (Wang et al, ).…”
Section: Regulation Of Rhoa Activity and Expressionmentioning
confidence: 99%
“…In addition, miR‐146a suppresses RhoA expression in MDA‐MB231 cells (Liu et al, ). Another microRNA, miR‐31, also reduced RhoA expression in gastric cancer cells MKN‐45 (Korourian, Roudi, Shariftabrizi, & Madjd, ). Loss of miR‐122 was also shown to be associated with poor prognosis in hepatocellular carcinoma progression along with cell migration and invasion and interestingly, RhoA 3′ UTR may be a binding site for miR‐122 (Wang et al, ).…”
Section: Regulation Of Rhoa Activity and Expressionmentioning
confidence: 99%
“…In this study, we suggested that miR‐31 was related to the 5‐FU resistance in colorectal cancer. There are some reports that miR‐31 is related to the 5‐FU resistance in colorectal cancer . Korourian et al and Li et al reported that miR‐31 targeted RhoA, and a long non‐cording RNA for 5‐FU resistance, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of miR-939, miR-623, miR-429, miR-204, miR-124 or miR-31 was shown to enhance 5-FUinduced chemosensitivity by compromising tumor cell growth or inducing apoptosis. 9,[13][14][15][16][17][18][19] Among the above-mentioned miRNAs, miR-939 and miR-204 were the only two miRNAs with confirmed ability of reversing drug resistance both in vitro and in vivo, providing more convening evidence than others. 9,15 A role of miR-31 in chemosensitivity was reported by two separate research groups and may have more obvious effects.…”
Section: Microrna-based Chemotherapy Fluorouracil Resistancementioning
confidence: 98%
“…9,15 A role of miR-31 in chemosensitivity was reported by two separate research groups and may have more obvious effects. [17][18][19] Moreover, reduced miR-6785-5p, miR-193-3p, or miR-147 expression could also increase the chemosensitivity of GC to 5-FU. [20][21][22] Interestingly, miR-193-3p and miR-147 both target phosphatase and tensin homolog (PTEN) to exert their functions in GC.…”
Section: Microrna-based Chemotherapy Fluorouracil Resistancementioning
confidence: 99%